At Home with the Diplomats : Inside a European Foreign Ministry - Neumann, Iver B. (Book collections on Project MUSE., 2012)
The 2010 WikiLeaks release of 250,000 U.S. diplomatic cables has made it eminently clear that there is a vast gulf between the public face of diplomacy and the opinions and actions that take place behind embassy doors. In At Home with the Diplomats, Iver B. Neumann offers unprecedented access to the inner workings of a foreign ministry. Neumann worked for several years at the Norwegian Ministry of Foreign Affairs, where he had an up-close view of how diplomats conduct their business and how they perceive their own practices. In this book he shows us how diplomacy is conducted on a day-to-day basis. Approaching contemporary diplomacy from an anthropological perspective, Neumann examines the various aspects of diplomatic work and practice, including immunity, permanent representation, diplomatic sociability, accreditation, and issues of gender equality. Neumann shows that the diplomat working abroad and the diplomat at home are engaged in two different modes of knowledge production. Diplomats in the field focus primarily on gathering and processing information. In contrast, the diplomat based in his or her home capital is caught up in the seemingly endless production of texts: reports, speeches, position papers, and the like. Neumann leaves the reader with a keen sense of the practices of diplomacy: relations with foreign ministries, mediating between other people's positions while integrating personal and professional into a cohesive whole, adherence to compulsory routines and agendas, and, above all, the generation of knowledge. Yet even as they come to master such quotidian tasks, diplomats are regularly called upon to do exceptional things, such as negotiating peace. -- Publisher description.